Weight change in middle adulthood and risk of cancer in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. Issue 7 (9th November 2020) - Christakoudi, Sofia; Pagoni, Panagiota; Ferrari, Pietro; Cross, Amanda J.; Tzoulaki, Ioanna; Muller, David C.; Weiderpass, Elisabete; Freisling, Heinz; Murphy, Neil; Dossus, Laure; Turzanski Fortner, Renee; Agudo, Antonio; et al.
Abstract: Obesity is a risk factor for several major cancers. Associations of weight change in middle adulthood with cancer risk, however, are less clear. We examined the association of change in weight and body mass index (BMI) category during middle adulthood with 42 cancers, using multivariable Cox proportional hazards models in the European Prospective Investigation into Cancer and Nutrition cohort. Of 241 323 participants (31% men), 20% lost and 32% gained weight (>0.4 to 5.0 kg/year) during 6.9 years (average). During 8.0 years of follow‐up after the second weight assessment, 20 960 incident cancers were ascertained. Independent of baseline BMI, weight gain (per one kg/year increment) was positively associated with cancer of the corpus uteri (hazard ratio [HR] = 1.14; 95% confidence interval: 1.05‐1.23). Compared to stable weight (±0.4 kg/year), weight gain (>0.4 to 5.0 kg/year) was positively associated with cancers of the gallbladder and bile ducts (HR = 1.41; 1.01‐1.96), postmenopausal breast (HR = 1.08; 1.00‐1.16) and thyroid (HR = 1.40; 1.04‐1.90). Compared to maintaining normal weight, maintaining overweight or obese BMI (World Health Organisation categories) was positively associated with most obesity‐related cancers. Compared to maintaining the baseline BMI category, weight gain to a higher BMI category was positively associated with cancers of the postmenopausal breast (HR = 1.19; 1.06‐1.33), ovary (HR = 1.40; 1.04‐1.91), corpus uteri (HR = 1.42; 1.06‐1.91), kidney (HR = 1.80; 1.20‐2.68) and pancreas in men (HR = 1.81; 1.11‐2.95). Losing weight to a lower BMI category, however, was inversely associated with cancers of the corpus uteri (HR = 0.40; 0.23‐0.69) and colon (HR = 0.69; 0.52‐0.92). Our findings support avoiding weight gain and encouraging weight loss in middle adulthood. Abstract : What's new? Obesity is well known as a risk factor for multiple cancers. What about gaining or losing weight mid‐life? Here, the authors investigated the association between cancer and change in weight and BMI category during mid‐life. Among 241, 323 people, about a third gained weight and 20% lost weight during the study. Independent of starting weight, gaining weight was associated with several obesity‐related cancers including cancers of the gallbladder, uterus, ovary, kidney, thyroid, breast after the menopause and in men pancreas. Losing weight was inversely associated with obesity‐related cancers overall, and specifically colon and uterine cancer. The authors conclude that public health interventions to support weight loss in middle age could help reduce cancer incidence.